The Recombinant Vaccinia Virus Gene Product, B18R, Neutralizes Interferon Alpha and Alleviates Histopathological Complications in an HIV Encephalitis Mouse Model - Fritz-French, Cari (Mary Ann Liebert, Inc., 2014)
Interferon-alpha (IFN-α) has been identified as a neurotoxin that plays a prominent role in human immunodeficiency virus (HIV)-associated neurocognitive disorders and HIV encephalitis (HIVE) pathology. IFN-α is associated with cognitive dysfunction in other inflammatory diseases where IFN-α is upregulated. Trials of monoclonal anti-IFN-α antibodies have been generally disappointing possibly due to high specificity to limited IFN-α subtypes and low affinity. We investigated a novel IFN-α inhibitor, B18R, in an HIVE/severe combined immunodeficiency (SCID) mouse model. Immunostaining for B18R in systemically treated HIVE/SCID mice suggested the ability of B18R to cross the blood–brain barrier (BBB). Real-time PCR indicated that B18R treatment resulted in a decrease in gene expression associated with IFN-α signaling in the brain. Mice treated with B18R were found to have decreased mouse mononuclear phagocytes and significant retention of neuronal arborization compared to untreated HIVE/SCID mice. Increased mononuclear phagocytes and decreased neuronal arborization are key features of HIVE. These results suggest that B18R crosses the BBB, blocks IFN-α signaling, and it prevents key features of HIVE pathology. These data suggest that the high affinity and broad IFN-α subtype specificity of B18R make it a viable alternative to monoclonal antibodies for the inhibition of IFN-α in the immune-suppressed environment.